Surgical pneumatization through maxillary sinus wall and the schneiderian membrane: A new technique to facilitate augmentation of the maxillary sinus - Anders-Petter Carlsson; Mohammad Kharazmi; Andreas Thor (Wolters Kluwer Medknow Publications, 2017)
A minimum subantral bone height in the posterior maxilla may require a bone augmentation where a sinus lift procedure is the most commonly used technique, either preceding or simultaneously with the implant installation. While elevating the Schneiderian membrane ruptures are common, possibly resulting in less bone formation. In this paper, we propose the surgical pneumatization of the Schneiderian membrane as a new technique to minimize the risk of such complications. This can be achieved mainly by creating a hole for the immediate and increased passage of air through the Schneiderian membrane and the maxillary sinus wall above the region of augmentation.